Crack path selection at the interface of wrought and wire + arc additive manufactured Ti–6Al–4V - Zhang, Jikui; Zhang, Xiang; Wang, Xueyuan; Ding, Jialuo; Traoré, Yéli; Paddea, Sanjooram; Williams, Stewart W. (Elsevier, 2016)
Crack propagation deviation tendency in specimens containing an interface between wrought alloy substrate and Wire + Arc Additive Manufacture (WAAM) built Ti–6Al–4V is investigated from the viewpoints of microstructure, residual stress and bi-material system. It is found that a crack initiated at the interface tends to grow into the substrate that has equiaxed microstructure and lower resistance to fatigue crack propagation. Experimental observations are interpreted by finite element modelling of the effects of residual stress and mechanical property mismatch between the WAAM and wrought alloy. Residual stresses retained in the compact tension specimens are evaluated based on measured residual stress in the initial WAAM built wall. Cracks perpendicular to the interface kept a straight path owing to the symmetrical residual stress distribution. In this case the tangential stress in bi-material model is also symmetric and has the maximum value at the initial crack plane. In contrast, cracks parallel to the interface are inclined to grow towards the substrate due to the mode II (or sliding mode) stress intensity factor caused by the asymmetric residual stress field. Asymmetric tangential stress in the bi-material model also contributes to the observed crack deviation trend according to the maximum tangential stress criterion.
Keywords: Additive manufacturing; Titanium alloy; Crack path selection; Microstructure; Residual stress; Bi-material; Finite element model